Elevated C-reactive protein and D-dimer to predict venous thromboembolism in patients with bladder cancer - Chen, Bo; Zhang, Tonghe; Wang, Yisong; Li, Zhaoyang; Liu, Haoyu; Jiang, Zhan; Yang, Huitang; Cai, Yandong; Fan, Guoju; Wang, Kaiqiang; Zhang, Hongwei; Hu, Hailong; et al. (Frontiers in Immunology, 2025)
ObjectiveThis study evaluated C-reactive protein (CRP) in hospitalized patients with bladder cancer (BC) and explored the predictive value of CRP for venous thromboembolism (VTE), combining CRP and D-dimer (D-D) levels to improve the ability to predict the risk of VTE in BC patients, thereby better guiding clinical prevention and treatment of this disease.MethodsClinical data from 4,438 patients with BC admitted between January 2015 and December 2020 were reviewed. After screening, 2,164 patients remained.52 VTE cases were identified, and 104 matched controls were selected (1:2 ratio). Conditional logistic regression, receiver operating characteristic (ROC) curve analysis, stratified analysis, and interaction tests were conducted to assess predictive performance and control for confounding bias.ResultsConditional logistic regression analysis indicated that elevated CRP and D-D levels were associated with higher risk of VTE in hospitalized patients with BC. Moreover, the areas under the ROC curves were 0.734 for CRP, 0.817 for D-D, and 0.865 for the combined model, indicating that the combined model offers superior predictive performance. Stratified and interaction analyses further revealed that the predictive value of CRP and D-D levels was influenced by the infection status.ConclusionElevated CRP and D-D levels may be potential indicators of VTE in BC patients. Their combined use improves predictive accuracy, and their predictive value may be better in non-infected patients.